Phytochemical competence and pharmacological perspectives of an endangered boon—Costus speciosus (Koen.) Sm.: a comprehensive review - Saima Sohrab (SpringerOpen, 2021)
Abstract Background Costus speciosus (Koen) Sm. popularly known as crepe ginger or spiral ginger and insulin plant is a perennial rhizomatous herb contain variable number of medicinally important bioactive phytochemicals having intensive pharmacological effects due to antioxidant, antimicrobial, insecticidal, anticancerous, and antidiabetic properties. This plant is widely distributed throughout India and has tremendous ethnobotanical uses. This review article is the coalescence of the distribution, morphology, phytochemistry, pharmacology, effect, and mode of action of pharmacologically active principles of Costus speciosus. Main body The therapeutic potential possessed by the plant is mainly the attribution of the bioactive compounds such as phenolics, steroids, alkaloids, flavonoids, saponins, terpenoids, and tannins, which are found to be present in different parts of the plant. Bioactive constituents like diosgenin, gracillin, dioscin, prosapogenins A and B of dioscin, eremanthin, costunolide, β-sitosterol, β-D-glucoside, β-carotene, α-tocopherol quinine, dihydrophytylplastoquinone, 5α-stigmast-9(11) en3β-ol, tetracosanyl octadecanoate, methyl hexadecanoate, methyl octadecanoate, cycloartenol, cycloartanol, and cycloalaudenol are specifically found in C. speciosus. This review also focuses on the possible mechanisms followed by these bioactive compounds while exhibiting various pharmacological properties. Because of the presence of diosgenin, this plant is given the name “insulin plant.” Diosgenin along with an important sesquiterpene, costunolide, performs significantly high antioxidant, anticancer, and antidiabetic activities. Besides these properties, insecticidal, antifungal, antibacterial, and anthelminthic properties have also been discussed. This plant needs to be given more emphasis as it is exploited at the commercial level by the pharmaceutical industries, conservation status is getting poorer, and it is already in a near-threatened state. Therefore, more systematic and intensive research should be done in a sustainable manner. Conclusion Spiral ginger plant shows diverse pharmacological effects due to presence of variety of bioactive phytochemicals, but the compounds like diosgenins, costunolides, eremanthin, and arbusculin are highly specific that exhibit effective antidiabetic, anticancerous, and antioxidative properties through different mechanism. Thus, C. speciosus can be exploited as an economically sustainable source of effective drugs against deadly diseases like diabetes and cancers with less or no side effects, and further research is needed to explore the intricacy of its pharmacological actions with human trials. Graphical Abstract